Factors Influencing Student Reading Achievement Based on Programme for International Student Assessment 2018 Dataset for Vietnam - PHOMMATHAN, Siphone (Souphanouvong University Journal Multidisciplinary Research and Development, 2024)
Students at all education levels rely on reading literacy to drive their improvement in other subjects. Meanwhile, reading remains not easy to be comprehensive for all students. Specifically, students’ reading comprehension could be influenced by student level factor. The student-level factor is parents’ emotional support since it contributes to improving students’ academic performance. In addition, enjoyment of reading can be a factor that affects students’ reading comprehension. Significantly, competitiveness in studying influences students to try to work harder, which assists them in improving their academic performance. Hence, this study investigated whether student-level factors-parents’ emotional support, enjoyment of reading and competitiveness influence students’ reading achievement. In this cross-sectional study, a quantitative research method was employed to identify and investigate the factors that influence the outcome of interest (i.e. students’ reading achievement). First, survey questionnaires were validated by using confirmatory factor analysis. In addition, reliability (Cronbach’s alpha) was analysed by using Statistical Package for Social Sciences (version 22) software. Structural equation modelling was employed to explain the relationship between the student-level variables. The analysis results showed that all student-level factors, except parents’ emotional support, had a significantly direct effect on students’ reading performance. Moreover, among these factors, enjoyment of reading had the greatest impact on their reading achievement. The findings of this study suggest that 15-year-old Vietnamese students’ achievement in reading are significantly influenced by multiple factors, both direct and indirect. This finding indicates that all students must be encouraged to engage in an enjoyable, constructive and competitive learning environment. It would be beneficial for future research to use a wide range of information and a qualitative research approach. Last, the implications of the findings of this thesis for educational policies, practice and theory are also discussed.